ETIK PENDISTRIBUSI GAS BERSUBSIDI DI KOTA PEKANBARU - Annisa Fajriatul Rahmi; Zaili Rusli SD (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
3 kg LPG gas is a government-subsidized gas whose purpose is for the poor and IKM. In Pekanbaru City the use of subsidized gas has been implemented since 2009 with the Pekanbaru area which is quite extensive and the large number of scattered bases has caused the problem of subsidized gas distribution not to be implemented properly. To overcome the problems of the government and the trade office and the Pekanbaru city and related parties set a code of ethics. The code of ethics is a rule that is made to reduce violations committed by the base so that the target of the distribution of subsidized gas is right. Responsibility, freedom, honesty, justice and autonomy are indicators of success in a profession. The purpose of this study was to find out how the code of ethics for the distribution of subsidized gas in the city of Pekanbaru, and the inhibiting factors. The concept of theory used in this study is the theory of professional ethics proposed by Keraf in the book Rismawaty. This study uses qualitative methods with descriptive data assessment. In compiling research data using purposive sampling method and incidental sampling as information and data analysis. The results showed that the code of ethics for the distribution of subsidized gas in the city of Pekanbaru is not yet running with a maximum of many bases that do not distribute according to the code of ethics that have been set. Keywords: Code of Ethics, Professional Ethics, Subsidized Gas